Characterization And Study Of Iron(III)-Released From Alginate/Zeolite/Fe Composite - Nia Silvia Sukma; Yateman Arryanto; Sutarno Sutarno (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
Alginate is an organic polymer that is isolated from brown algae and bacteria, while the zeolite is an aluminosilicate mineral sample. The purpose of this study was to synthesize composite alginate / zeolite / Fe, characterize composite alginate / zeolite / Fe, and assessing the release properties of Fe (III) of the composite alginate / zeolite / Fe. Characterization of the composite is done by observing the color composite macroscopically, and observing the pattern of distribution of zeolite particles in composites using SEM (Scanning Electron Microscope). As for assessing the release of Fe (III) of the composite system made by soaking the composite in a solution of citric acid 0,33M for nine hours. Components of Fe (III) were dissolved in acid systems were analyzed using UV-Vis spectrophotometer.The results showed that the composite alginate / zeolite / Fe have colors that are significantly dependent on the component ratio of alginate and zeolitnya. SEM analysis provides information that the zeolites distributed evenly on alginate-Fe phase. The release profile of Fe (III) of the composite alginate / zeolite / Fe weight variation component alginate produced three mechanisms to increase and decrease the rate of release of Fe (III). While the release profile of Fe (III) of the composite alginate / zeolite / Fe by weight of the zeolite component generates two mechanisms that increase and decrease the rate of release of Fe (III).